2015
DOI: 10.1785/0120140309
|View full text |Cite
|
Sign up to set email alerts
|

Hypocenters in the Nankai Trough Determined by Using Data from Both Ocean‐Bottom and Land Seismic Networks and a 3D Velocity Structure Model: Implications for Seismotectonic Activity

Abstract: We investigated the hypocenter distribution along the Nankai trough off the Kii Peninsula, Japan, by using data from both ocean-bottom and land-based seismic networks. Because seismic velocity structures differ greatly below land and ocean, we used a 3D velocity model based on a structural model of the Philippine Sea plate (PHS), which provides much more accurate estimations of source locations than 1D velocity models derived from either onshore or ocean-bottom seismic data alone, especially for sources betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
(68 reference statements)
2
13
0
Order By: Relevance
“…The largest residuals are found southeast off Kii Peninsula, near 137°E. This may be caused by postseismic deformation of the M w 7.2 and M w 7.4 earthquakes off Kii Peninsula on 26 September 2004, which was an intraslab event in the subducting plates (Nakano et al, 2015) (Fig. 3B).…”
Section: Resultsmentioning
confidence: 95%
“…The largest residuals are found southeast off Kii Peninsula, near 137°E. This may be caused by postseismic deformation of the M w 7.2 and M w 7.4 earthquakes off Kii Peninsula on 26 September 2004, which was an intraslab event in the subducting plates (Nakano et al, 2015) (Fig. 3B).…”
Section: Resultsmentioning
confidence: 95%
“…Oceanfloor observations in the Tonankai region also could not detect earthquakes on the PHS interface ( Fig. 7 of Nakano et al 2015). However, on April 1, 2016, a shallow moderate earthquake suddenly occurred at the southeast offshore Mie prefecture, Kii Peninsula, Japan.…”
Section: Introductionmentioning
confidence: 94%
“…1 and Additional file 1: Figure S1) has facilitated continuous monitoring of offshore seismic activities Kawaguchi et al 2015). These observations revealed that, in recent years, earthquake activities along the Nankai Trough have mostly occurred in the oceanic crust or upper mantle of the subducting PSP (Obana et al 2004Obana and Kodaira 2009;Mochizuki et al 2010;Akuhara et al 2013;Nakano et al 2013Nakano et al , 2014Nakano et al , 2015Akuhara and Mochizuki 2014). The most recent notable events during this time have been the 2004 M JMA 7.1, 7.4, and 6.5 earthquakes off the Kii Peninsula, which occurred in the subducting plate (e.g., Sakai et al 2005;Seno 2005).…”
Section: Introductionmentioning
confidence: 95%
“…The simulation implies that the M6-class off-Mie earthquake was caused by shrinkage of the strongly coupled area along the plate boundary. Present seismic activities in the eastern Nankai Trough are mostly within the subducting or overriding plates, and there is very low activity in the rupture area of the megathrust earthquakes (Obana et al 2004;Obana and Kodaira 2009;Nakano et al 2015). However, Akuhara and Mochizuki (2014) observed continuous activity of an earthquake cluster with magnitudes smaller than 4 along the plate boundary west of the Kii Peninsula (labeled "A" in Fig.…”
Section: Earthquake Cycle Simulation Based On the Hierarchical Asperimentioning
confidence: 99%